Editor’s Introduction - Saidatulakmal Mohd,; Hooi Hooi Lean, (Kajian Malaysia, 2015)
This special issue of Kajian Malaysia is titled "Sustainable Economic Development: Policies and Strategies" with central attention to the cases of Malaysia. This special issue consists of 12 refereed papers, all of which were originally presented at the USM-AUT International Conference 2012, jointly organised by Universiti Sains Malaysia and Auckland University of Technology from 17–18 November 2012, held at the Bayview Beach Resort, Pulau Pinang, Malaysia. The conference benefited from the support of the Japan Foundation Kuala Lumpur (JFKL), Brawijaya University, Malang, Indonesia, Scientific Academic Publishing and Emerald Publishing. The conference objectives are to provide an interdisciplinary forum on the policies and strategies related to sustainable economic development for academics and practitioners; to propose multidisciplinary strategies for economic, socio-political, cultural and institutional changes to achieve sustainable economic development; to discuss the practical challenges faced in promoting sustainable economic development; and to provide a platform to share ideas, experiences and research results about all aspects related to sustainable economic development.